2020
DOI: 10.1017/s1751731120000890
|View full text |Cite
|
Sign up to set email alerts
|

Reducing protein content in the diet of growing goats: implications for nitrogen balance, intestinal nutrient digestion and absorption, and rumen microbiota

Abstract: Reducing dietary CP content is an effective approach to reduce animal nitrogen excretion and save protein feed resources. However, it is not clear how reducing dietary CP content affects the nutrient digestion and absorption in the gut of ruminants, therefore it is difficult to accurately determine how much reduction in dietary CP content is appropriate. This study was conducted to investigate the effects of reduced dietary CP content on N balance, intestinal nutrient digestion and absorption, and rumen microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
9
1
Order By: Relevance
“…In the rumen, Synergistetes is known for its capability to degrade amino acids [21]. The decreased relative abundance of Synergistetes in the rumen of goat fed a low protein diet was also reported by Zhang et al [22]. The decreased apparent digestibility of CP in the LCP group observed in our previous study [4] could be partially explained by the reduced abundances of these protein-degrading bacteria.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 83%
“…In the rumen, Synergistetes is known for its capability to degrade amino acids [21]. The decreased relative abundance of Synergistetes in the rumen of goat fed a low protein diet was also reported by Zhang et al [22]. The decreased apparent digestibility of CP in the LCP group observed in our previous study [4] could be partially explained by the reduced abundances of these protein-degrading bacteria.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 83%
“…Creatine is enzymatically synthesized from glycine and arginine in the kidneys and liver ( Kreider et al, 2017 ). According to previous studies, concentrate contains significantly higher glycine and arginine contents at 4.9% and 7.6%, respectively ( Zhang et al, 2020 ) compared to alfalfa at 3.7% and 5.3%, respectively ( Giner‐Chavez et al, 1997 ). We, therefore, postulated that the high glycine and arginine content in concentrate may have contributed to creatine synthesis in the loin meat from the KLA group, which was then non-enzymatically transformed into creatinine.…”
Section: Resultsmentioning
confidence: 87%
“…CoQ 10 can be endogenously synthesized by a process including the synthesis of the benzoquinone ring from tyrosine as a precursor ( Bank et al, 2011 ). Although we did not perform a complete amino acid composition analysis for alfalfa and concentrate, alfalfa contains 3.3%–4.17% tyrosine ( Brito et al, 2014 ; Giner‐Chavez et al., 1997 ; Kaldy et al, 1980 ), while concentrate for goat feed has 2.87% tyrosine ( Zhang et al, 2020 ). We, therefore, postulated that the high tyrosine content in alfalfa might be related to CoQ 10 synthesis in the loin meat of the KHA group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al ( 2019 ) suggested that gastrointestinal tract microbial communities influences the utilization efficiency of nitrogen in goats. Zhang et al ( 2020b ) reported that reducing dietary CP content by 3% diminished the relative richness of Bacteroidetes, which might be associated with the increasing efficiency of carbohydrate utilization in the rumen. Most previous studies have concentrated on how protein levels affect ruminal microbiota, and the influence of different plant protein sources on ruminal bacterial communities has relatively not been examined.…”
Section: Introductionmentioning
confidence: 99%